Selective production of phase-separable product from a mixture of biomass-derived aqueous oxygenates - Yehong Wang (Nature Portfolio, 2018)
The efficiency and selectivity of the transformation process for an aqueous solution of mixed oxygenates produced by biomass fermentation remains a challenge. Here, the authors report a simple reaction for the conversion of aqueous biomass fermentation broth to a water-immiscible product efficiently and selectively.